Anti-tumoral activity of the Pan-HER (Sym013) antibody mixture in gemcitabine-resistant pancreatic cancer models. Issue 1 (1st January 2021) - Rabia, Emilia; Garambois, Véronique; Hubert, Julie; Bruciamacchie, Marine; Pirot, Nelly; Delpech, Hélène; Broyon, Morgane; Theillet, Charles; Colombo, Pierre-Emmanuel; Vie, Nadia; Tosi, Diego; Gongora, Celine; et al.
ABSTRACT: Chemoresistance, particularly to gemcitabine, is a major challenge in pancreatic cancer. The epidermal growth factor receptor (EGFR) and human epidermal growth factor receptors 2 and 3 (HER2, HER3) are expressed in many tumors, and they are relevant therapeutic targets due to their synergistic interaction to promote tumor aggressiveness and therapeutic resistance. Cocktails of antibodies directed against different targets are a promising strategy to overcome these processes. Here, we found by immunohistochemistry that these three receptors were co-expressed in 11% of patients with pancreatic adenocarcinoma. We then developed gemcitabine-resistant pancreatic cancer cell models (SW-1990-GR and BxPC3-GR) and one patient-derived xenograft (PDX2846-GR) by successive exposure to increasing doses of gemcitabine. We showed that expression of EGFR, HER2 and HER3 was increased in these gemcitabine-resistant pancreatic cancer models, and that an antibody mixture against all three receptors inhibited tumor growth in mice and downregulated HER receptors. Finally, we demonstrated that the Pan-HER and gemcitabine combination has an additive effect in vitro and in mice xenografted with the gemcitabine-sensitive or resistant pancreatic models. The mixture of anti-EGFR, HER2 and HER3 antibodies is a good candidate therapeutic approach for gemcitabine-sensitive and -resistant pancreatic cancer.